Dozwolony podział przedmiotu zamówienia w świetle norm prawa krajowego i unijnego - Stokłosa, Paweł (Kwartalnik Prawa Publicznego, 2015)
This article discusses the problem connected with the division of the public procurement contract in the light of European Union legal norms and the Polish regulation. In practice, sometimes norms based on EU law as interpreted by the Court of Justice of the European Union are not applied in domestic procurements. One of the reasons of this phenomenon is unclear meaning of the polish regulation. Taking as an example the actual conditions, there are indicated faults which are consequence of problems with interpretation. Taken is also an attempt to find a reason of this phenomenon. The proposal to solve the problem is formulated as a conclusion de lege ferenda concerned to the domestic regulations.